Analysis of Flood Occurrence in Pekanbaru City Using Google Earth Engine - Rahmatul Irfan; Sutikno, Sigit; Yusa, Muhamad (Rekayasa Sipil, 2025)
The phenomenon of climate change is associated with various disasters in the community. During the year 2023, the city of Pekanbaru often experienced floods that were scattered at several locations, resulting in both material and non-material losses. To reduce the impact of losses incurred and flood disaster mitigation plans, it is necessary to map floods in Pekanbaru because information related to flood events is difficult to access and is known by the community. In this research, flood mapping uses one of the practical recommendation methods from UN-SPIDER, using Google Earth Engine and SAR-1 sentinel imagery; this method was chosen because it is efficient in both time and data in flood mapping. The results of flood mapping in Pekanbaru during 2021-2023 found that the largest area occurred in 2021, covering 2714 Ha, then in 2023, covering 867 Ha, and in 2022 covering 310 Ha. The threshold value specifically for the Pekanbaru city area is 1.17, known through the threshold value calibration, namely repeated testing by comparing the results of the area obtained. Validation of the results of the distribution model on flood mapping in the city of Pekanbaru used comparative data on flood event records from BWSS III and BPBD Pekanbaru city; the results of flood distribution in Google Earth Engine have the suitability of flood distribution prediction location points with actual flood disaster record points.